Safety and efficacy of IMP (disodium 5′‐inosinate) produced by fermentation with Corynebacterium stationis KCCM 80161 for all animal species. (27th May 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of disodium 5′‐inosinate (IMP) produced by fermentation using Corynebacterium stationis KCCM 80161 when used as a sensory additive (flavouring compound) in feed and water for drinking for all animal species. The production strain is not genetically modified. Viable cells of the production strain were not detected in the final additive. The additive does not give rise to any safety concern regarding the production strain. IMP produced using C. stationis KCCM 80161 is considered safe for the target species, for the consumer and for the environment. IMP produced using C. stationis KCCM 80161 is considered not toxic by inhalation, not irritant to skin or eyes and not a dermal sensitiser. The FEEDAP Panel expressed reservations on the use of the additive in water for drinking due to concerns on its impact on the hygienic conditions of the water. The Panel concluded that the additive is efficacious to contribute to the flavour of feed.